Emergency surgery in an elective setting: a case report detailing incidental diagnosis of a de Garengeot hernia. Issue 6 (15th June 2020) - Brosnan, Conor; Keogh, Shane; Bolger, Jarlath C; Farrell, Kevin; Hannan, Enda; Mulholland, Doug; Butt, Abeeda; Hill, Arnold D K
Abstract: We present a case of acute appendicitis within an incarcerated femoral hernia. This is a rare complication of the phenomenon eponymously known as a 'De Garengeot Hernia', which describes a vermiform appendix in an incarcerated femoral hernia sac. Our case is somewhat unique in the manner by which the affected patient had presented. Attending hospital for an unrelated elective surgery, an incarcerated hernia was diagnosed at time of admission. Thorough assessment in advance of the procedure and decisive action led to a satisfactory outcome. This may be the first case in literature reporting a 'De Garengeot Hernia' presenting in such a fashion.